BUDAYA ORGANISASI ISLAMI SEBAGAI FONDASI MANAJEMEN LEMBAGA PENDIDIKAN BERKUALITAS - Oman Fathurohman; Siti Nur Fazriyah (Universitas Islam Bunga Bangsa Cirebon, 2023)
Organizational culture constitutes one of the most powerful yet frequently underestimated determinants of educational quality in Islamic educational institutions. While considerable scholarly attention has been directed toward structural and technical dimensions of educational quality management, the role of Islamic organizational culture as a foundational driver of institutional excellence remains insufficiently theorized and empirically validated in the Indonesian Islamic education management literature. This study investigates Islamic organizational culture as the foundational basis for quality management in Islamic educational institutions, pursuing three objectives: (1) to analyze the conceptual dimensions of Islamic organizational culture and its theoretical relationship with educational quality, (2) to examine the mechanisms through which Islamic organizational culture influences institutional management quality, and (3) to construct a model of Islamic organizational culture development that serves as a strategic foundation for educational quality improvement. Employing a systematic library research methodology drawing on thirty-four peer-reviewed sources published between 2020 and 2022, the study proposes the Tawhidic Organizational Culture Framework (TOCF), a six-dimensional model integrating Islamic values of tawhid, amanah, shura, itqan, tawadhu, and ukhuwah as cultural pillars of quality Islamic educational management.